METHODOLOGY OF STUDYING INTERNATIONAL ECONOMIC PROCESSES: CONTEXT OF THE PREPARATION OF UKRAINE’S POST-WAR ECONOMIC RECOVERY PROGRAMME - SHAROV, Oleksandr (Journal of European Economy, 2022)
The article discusses the issues of the methodology of studying of international relations on the example of the preparation of the Programme for the Post-War Economic Recovery of Ukraine. Since the preparation of such a programme includes a preliminary determination of the potential place of Ukraine in the new global economy, the consideration of international geo-economic relations in such a programme is quite logical. This brings forth the problem of using modern methods to study such relationships. Considering the general problems of this topic, the author focuses on the methodological approaches to the study of the strategy of the activities of international financial groups in the Ukrainian market in the conditions of post-war recovery of the economy. This is one of the research components aimed at determining the potential place of Ukraine in the global economy. In particular, the author provides his own definition of international financial groups and highlights changes and adjustments that should be made and used in connection with a non-standard situation caused by both the Coronavirus pandemic and war against Ukraine. JEL: B41, F60, G10, G20.